2012
DOI: 10.1136/jech-2011-200754
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in incidence, survival and mortality from abdominal aortic aneurysm in New Zealand

Abstract: Ethnic variation in the incidence, mortality and cumulative relative survival from AAA in NZ resembles ethnic inequalities in other health outcomes. This provides additional support for screening on equity grounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Population-based studies of other cardiovascular diseases and mortality rates have indicated a declining or stable trend 9,12,13,15,16,36 , which supports the present findings. More than half of the observed CHD mortality decrease in Sweden between 1986 and 2002 was attributable to reductions in major risk factors (blood pressure, cholesterol, smoking) 37 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Population-based studies of other cardiovascular diseases and mortality rates have indicated a declining or stable trend 9,12,13,15,16,36 , which supports the present findings. More than half of the observed CHD mortality decrease in Sweden between 1986 and 2002 was attributable to reductions in major risk factors (blood pressure, cholesterol, smoking) 37 .…”
Section: Discussionsupporting
confidence: 90%
“…Intervention rates depend on several factors such as prevalence, diagnostic intensity in the community (for example organized or opportunistic screening) and access to vascular surgical units 8,9 . In several regions worldwide men are offered screening by ultrasonography, as long-term follow-up regarding the efficacy of screening programmes has shown an approximately 40 per cent reduction in AAA-associated mortality 5,8,10 -12 . An unexpectedly low incidence of AAA has been found in recent screening reports 12,13 in contrast to the reported increasing intervention rates for AAA in Europe 9,12,14 . A decrease in incidence and mortality from coronary heart disease (CHD) in Sweden (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) has been reported 15,16 , and it is not known whether there is a similar trend for AAA.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…First and foremost, it was intended to investigate results separately for Maori (the indigenous population group in New Zealand) and non‐Maori. There is good consensus from New Zealand studies that the AAA mortality rate is about twice as high in Maori as in non‐Maori, and Maori also appear to present with AAA disease at younger ages. The drivers of higher AAA mortality in Maori are unclear; it could be due to any combination of a range of potential factors: higher AAA prevalence, poorer incidental detection, faster growth or higher rupture rates, lower likelihood of being offered or being eligible for elective or emergency repair, poorer outcomes after elective and emergency repair, or lower likelihood of reaching hospital in time after AAA rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Male sex is associated with increased risk of AAA. In New Zealand, about one in 74 men aged over 65 years dies from AAA, despite an apparent declining incidence and mortality rate from the disease. AAA screening models have been implemented in the UK and Sweden, which exclusively examine men over the age of 65 years.…”
Section: Introductionmentioning
confidence: 99%